Analisis cara belajar tema berbagai pekerjaan di rumah pada peserta didik kelas IV Sekolah Dasar - Cysha Dyah Ayu Saraswati; Sukarno Sukarno; Muhammad Ismail Sriyanto (Universitas Sebelas Maret, 2021)
This research aim is to find student's learning methods at home, the obstacles encountered while students studying at home, and the solutions to these obstacles. This research using descriptive qualitative research methods and using a phenomenological approach. The data sources in this research are students of 4th SDN Bayan Purworejo and studet’s parents. Data collection techniques were carried by questionnaires, interviews, and documentation studies, and data validity testing using technical triangulation and source triangulation. Data are analyzed by Miles and Huberman data analysis model. The results of this research indicate that while studying at the homes, the student’ learning methods are to make schedules and implement them, read books, take notes, and do assignments. When studying at home, students encounter several obstacles, there are limited learning support tools, low discipline to learn, and difficulty in understanding the material. To overcome these obstacles, the solutions are implementing study group activities with restrictions of students in the group, parents are firm in making schedules so that student's daily activities can be controlled, and if the students can't understand the material can ask their parents/siblings/class teacher. The results of this research can also be used to increase students' insights about learning methods that can be used at home, bases of relevant research, and reference for parents to make improvements in learning facilities and learning quality so student's learning processes are better and can improve learning output.